Extraction Process and Physics Chemical Characterization of Agar Powders from Gracilaria sp. Laboratory Scale in PT. Java Biocolloid Surabaya. - Nidya Tria Yolanda; Agustono Agustono (Universitas Airlangga, 2018)
Seaweed is one of the sea commodities have high economic value, because of extensive utilization, in daily activity as well as in the industrial world, so it has a vast domestic market and abroad. Seaweed contains hidrocoloid compounds such as carrageenan, agar and alginate. It has the main product from Rhodophycae, such as Gracilaria,Gellidium. The purpose of Research is to determine the characteristics of chemical physics powdered agar fromGracilariasp. PT. Biocolloid Java, Surabaya. Activity Research will be implemented at PT. Java Biocolloid, Kembangan Sub-District, District Krembangan, Surabaya. This activity will be held on February 1 to February 26, 2016. The research methods used in Field Work Practice is descriptive method with data collection included primary data and secondary data. Data were collected by observation, interview, active participation, and literature. The of chemical physics powder to be conducted by the quality control, research and development PT. Java Biocolloid Surabaya include granulometri, turbidity, pH, gel strength, viscosity and water content. The value of granulometri powder that is 100% pass meshsize 60. The powder that has a turbidity value of 11.0 to 29.9 NTU, pH 6.4 to 6.8, the gel strength 800-1000 g / cm, viscosity 17-19 cP and moisture content 8- 11%. The quality of chemical physics powdered agar produced by PT. Java Biocolloid already meets the quality standards to be a good powder in accordance with the quality standards powdered agar by the consumer both nationally and internationally.